2018
DOI: 10.33776/et.v8i2.3591
|View full text |Cite
|
Sign up to set email alerts
|

Remarks From Tourism Planning and Sustainable Tourism - A Bibliometric Study

Abstract: Tourism is emphasized as one of the sectors with the greatest potential for expansion on a global scale; therefore, it is important to understand related factors regarding tourism planning and sustainability. The main contribution of this study is to identify research trends linked to the keywords, respective gaps and specific needs for future scientific research within the research field of tourism planning and sustainable development. Using VOSviewer Software and applying bibliometric techniques, visualizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 31 publications
1
3
0
1
Order By: Relevance
“…Results obtained are oposite to results of Mota et al 2018, since they found Tourism Management, Annals of Tourism Research and Journal of Sustainable Tourism on the first three places.…”
Section: Papers Published By Publishing Sourcesupporting
confidence: 62%
“…Results obtained are oposite to results of Mota et al 2018, since they found Tourism Management, Annals of Tourism Research and Journal of Sustainable Tourism on the first three places.…”
Section: Papers Published By Publishing Sourcesupporting
confidence: 62%
“…[12] used a modified Delphi technique to develop a total of 125 measurable regional tourism sustainable development indicators in six dimensions: political, social, ecological, economic, technological, and cultural dimensions. [13] proposed a system of indicators to evaluate the sustainable development of tourism in cultural tourism destinations in three dimensions: social, economic, and environmental, a composite indicator constructed based on a goal-based planning approach and illustrated with the example of a cultural tourism destination in the Andalusian region of Spain [14]. Based on the index system of literature search, a preliminary list of indicators was compiled and then validated by the Delphi method to establish a local level tourism sustainability evaluation index system including social and economic as well as environmental dimensions.…”
Section: Related Workmentioning
confidence: 99%
“…There is also a coincidence with the work of Estevão et al (2017) with the search words "tourism management" and "management of tourism" reported 402 articles with an increase in the number of publications from 2008 and the exponential trend was kept until 2016. For the search words "Sustainable Tourism" and "Tourism planning", the evolution of publications from 1997 to 2017 presented two profiles, the first of them with fewer than 150 articles published until 2007 and an exponential increase from 2008 to 2017 with an exponential trend (Mota et al, 2018). In summary, starting in 2008, there was a growth in the number of articles published on topics of tourism, tourism competitiveness, destination competitiveness, tourism destination competitiveness, tourism management, sustainable tourism and tourism planning.…”
Section: Discussionmentioning
confidence: 99%